Impact of Green Tea Catechin Ingestion on the Pharmacokinetics of Lisinopril in Healthy Volunteers - Shingen Misaka; Yuko Ono; Atsushi Uchida; Tomoyuki Ono; Osamu Abe; Hiroshi Ogata; Hideyuki Sato; Masahiko Suzuki; Satomi Onoue; Yayoi Shikama; Kenju Shimomura (Wiley, 2021)
Lisinopril, a highly hydrophilic long‐acting angiotensin‐converting enzyme inhibitor, is frequently prescribed for the treatment of hypertension and congestive heart failure. Green tea consumption may reduce the risk of cardiovascular outcomes and total mortality, whereas green tea or its catechin components has been reported to decrease plasma concentrations of a hydrophilic β blocker, nadolol, in humans. The aim of this study was to evaluate possible effects of green tea extract (GTE) on the lisinopril pharmacokinetics. In an open‐label, randomized, single‐center, 2‐phase crossover study, 10 healthy subjects ingested 200 mL of an aqueous solution of GTE containing ~ 300 mg of (-)‐epigallocatechin gallate, a major catechin component in green tea, or water (control) when receiving 10 mg of lisinopril after overnight fasting. The geometric mean ratio (GTE/control) for maximum plasma concentration and the area under the plasma concentration‐time curve of lisinopril were 0.289 (90% confidence interval (CI) 0.226-0.352) and 0.337 (90% CI 0.269-0.405), respectively. In contrast, there were no significant differences in time to reach maximum lisinopril concentration (6 hours in both phases) and renal clearance of lisinopril (57.7 mL/minute in control vs. 56.9 mL/minute in GTE). These results suggest that the extent of intestinal absorption of lisinopril was significantly impaired in the presence of GTE, whereas it had no major effect on the absorption rate and renal excretion of lisinopril. Concomitant use of lisinopril and green tea may decrease oral exposure to lisinopril, and therefore result in reduced therapeutic efficacy.